Entre mensagem e desígnio: o lugar do desenho industrial na FAUUSP em meados da década de 1960 - Fiammenghi, João Bittar (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2023)
This article aims to explore the meaning of adding the Industrial Design (ID) courses in the 1962 educational reform at the School of Architecture and Urbanism of the University of São Paulo (FAUUSP). From questioning official institutional documents and statements elaborated by its professors, two main issues were highlighted. First, the diversity of goals and intentions at the origin of the industrial design teaching in São Paulo, emphasizing the idea of the “total designer,” the expansion of design scales in the studios, and the problems around construction industrialization. Then, the text debates and contextualizes some statements made by Lucio Grinover in the mid-1960s, by bringing to the fore his bet on a new scientificity in design teaching made possible by the ID courses.